Chief Justice Rose Bird's State of the Judiciary Address at State Bar Annual Meeting - Watkins, Howard::::::::: (1985)
Incoming State Bar President David Heilbron, Outgoing State Bar President Burke Critchfield and Philip Hammer seated; Chief Justice Rose Bird speaking at lectern Seal of State Bar of California on lectern